Penerapan Data Mining Untuk Analisis Pengaruh Nilai Imla dan Nahwu Terhadap Nilai Bahasa Arab Di Pesantren - Nadiroh, Yahdinil Firdha (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2024)
Students in Islamic boarding schools often use Arabic as their daily language. It is even mandatory to use it to communicate. This requires students to study harder and memorize more Arabic vocabulary. This study aims to apply data mining using multiple linear regression methods to analyze the effect of Imla and Nahwu values on Arabic language values in female students in Islamic boarding schools. This study used samples of female students' values in Imla, Nahwu, and Arabic. This method is applied to identify the relationship and influence of the three values and whether they can affect the level of success in Arabic language lessons. With data mining, the influence and relationship between the three lessons can be determined. And with this study, it is expected to provide a positive contribution to Islamic boarding schools and similar educational institutions in efforts to improve the quality of Arabic language learning. In addition, the data mining method applied can be used as a reference for further research exploring further information about the determining factors for the success of learning Arabic in Islamic boarding schools.